Women in Novels Regarding Japanese Occupation: A Study of the Sociology of Literature - Ahmad Bahtiar; Gunta Wirawan; Hilmiyatun Hilmiyatun; Kundaru Saddhono (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2023)
The Japanese occupation government in the Indonesia carried out propaganda using various media, including literature. The propaganda often depicts the condition of women at that time. This study examines the picture of women in the Japanese occupation that has been reflected in four novels published in two eras: during and after the Japanese occupation. Novels published during the Japanese occupation were Palawidja by Karim Halim and Cinta Tanah Air by Nur Sutan Iskandar. Meanwhile, the novels published after the Japanese occupation were Dan Perang pun Usai by Ismail Marahimin and Kembang Jepun by Remy Sylado. The novels were approached by the sociology of literature by Alan Swingewood and Diana Laurenson. The research prove that the four novels have a different picture of women in the Japanese occupation. Women in novels written during the Japanese occupation are described as having a fate full of suffering, for example, in the novels Kembang Jepun and Dan Perang pun Usai. Meanwhile, women in novels written after the Japanese occupation are described as having a luckier fate, as seen in Palawidja and Cinta Tanah Air. These depictions came to differences in the activities, authorship background, and time interval of the writing of the four authors.